Validation of the Norwegian Pain Sensitivity Questionnaire - Valeberg, Berit Taraldsen (J Pain Res, 2017)
BACKGROUND AND PURPOSE: There is a large variation in people’s reactions to painful stimuli. Although some conditions are more painful, the variation between people is larger than the reaction to pain across conditions. Induced experimental pain is one way to assess some aspects of these differences in pain perception. Experimental nociceptive testing is time consuming and not always feasible in a clinical setting. In order to overcome the obstacles of assessing pain sensitivity using experimental stimulation, the Pain Sensitivity Questionnaire (PSQ) was developed. The purpose of this study is to validate the Norwegian version of the PSQ. METHODS: Construct validity was examined through an exploratory principal component factor analysis with varimax rotation. Internal consistency was measured by Cronbach’s alpha reliability for subscales and the total PSQ. As confounding variables such as age and gender may contribute to the experience of pain, a regression analysis was performed with demographic variables and PSQ scores as independent variables and the experimental measures of pain as the dependent variable. RESULTS: The factor analysis yielded at two factor solution, with an eigenvalue greater than one, explain 58% of the variance. Cronbach’s alpha for the PSQ was 0.92. In the regression analysis, only PSQ scores contributed to explain the experimental pain intensity and tolerance. Gender only influenced the experimental pain threshold, as men had statistically significant higher heat pain threshold than women. CONCLUSION: This study shows that PSQ is a valid and reliable questionnaire and might be a promising instrument for assessing pain sensitivity in Norwegian clinical settings. Further studies are needed to examine whether the PSQ can be used in clinical settings to predict postoperative pain and the development of chronic pain.